Factors Affecting Sources of Information Utilization (Indian Journal of Extension Education, 2013)
An attempt has been made to study the factors affecting information sources utilization by the farmers. The study was conducted with a sample of 300 farmers drawn randomly from Banka and Rajaun blocks of Banka district of Bihar. The study revealed that socio-economic status, interpersonal interaction, and value orientation were the main factors determining the sources of information utilized by farmers. The value of co-rrelation coefficient (r = 0.566) was found to be highest in case of socio-economic status, whereas the regression co-efficient was found to be highest (b=0.328) in case of interpersonal interaction.